Pemantauan dan Pengendalian Kekeruhan Air Kolam Pembibitan Ikan Lele Dengan PLC Outseal Berbasis IoT, Di Fardu Farm Pekanbaru - Akbar, Muhammad Razzaq; Zarory, Hilman; Mursyitah, Dian; Faizal, Ahmad (Forum Kerjasama Pendidikan Tinggi, 2024)
In catfish hatchery farming, monitoring and controlling water quality is essential to ensure optimal conditions for fish growth. One of the key parameters that need to be monitored is water turbidity, which can affect fish health and the quality of the water environment in the hatchery pond. Monitoring the turbidity of catfish hatchery ponds has generally been done manually by farmers, which has several significant drawbacks. This manual process is inefficient as it requires physical presence at the pond site and must be performed periodically, consuming time and labor. In this study, the researchers propose an innovative solution using an automated system based on the PLC Outseal Mega V3 and the BGT-D718-TDS sensor, connected with the Internet of Things (IoT) to monitor and control the turbidity of catfish hatchery ponds. This research integrates IoT technology into the automatic control of pond water turbidity, aiming to ease operational burdens in catfish farming. The results of a 14-day experiment showed that the system effectively controlled pond water turbidity, with significant reductions observed on day 12 by 4.4 ppm and on day 13 by 3.46 ppm. Thus, implementing IoT technology in water quality monitoring and control can be an important step in enhancing operational efficiency and sustainability in aquaculture.